Virtual screening of combinatorial library of novel benzenesulfonamides on mycobacterial carbonic anhydrase II - Dikant F.; Gáplovský F.; Garaj V. (Sciendo, 2016)
Combinatorial library of novel benzenesulfonamides was docked (Schrodinger Glide) into mycobacterial carbonic anhydrase (mtCA II) and human (hCA II) isoforms with an aim to find drug candidates with selective activity on mtCA II. The predicted selectivity was calculated based on optimized MM-GBSA free energies for ligand enzyme interactions. Selectivity, LogP (o/w) and interaction energy were used to calculate the selection index which determined the subset of best scoring molecules selected for further evaluation. Structure-activity relationship was found for fragment subsets, showing us the possible way regarding how to influence lipophilicity without affecting ligand-enzyme binding properties.